Resource-Efficient Technologies for Improvement of Land Reclamation and Ecological Condition - Rahimberdiyevich, Asatov Sayitqul; ogli, Sulaymonov Javokhir Nematjon; oglu, Muhamadov Kamoriddin Mukhtor; Utkirovich, Bobojonov Saidjon (European Journal of Life Safety and Stability (2660-9630), 2022)
This article focuses on the establishment of effective measures to identify and prevent adverse processes of the ameliorative-ecological state of irrigated lands of Bukhara Oasis. Recommendations have been made on improving ameliorative-ecological state of soil, maintaining, increasing productivity and their effective use, introduction of resource-saving technologies preventing secondary salinization.